Different behavioral strategies of two sympatric seahorses: habitat availability and increased density of Hippocampus guttulatus alter the behavior of Hippocampus hippocampus - Spatafora, Davide; Gristina, Michele; Quattrocchi, Federico; Pierri, Cataldo; Lazic, Tamara; Palma, Jorge (Frontiers in Marine Science, 2023)
In the light of future ocean warming scenarios and habitat fragmentation, coastal fishes must adjust their physiological and behavioral traits to face the combined effect of global warming and ecological interactions. Seahorses (Hippocampus spp.) are charismatic fishes with peculiar life cycle traits, which make them vulnerable to several anthropic pressures and natural disturbances. In this study, we investigated the behavior of two sympatric seahorse species, the long-snouted Hippocampus guttulatus (Cuvier, 1829) and the short-snouted Hippocampus hippocampus (Linnaeus, 1758). Specifically, we carried out two manipulative experiments to assess (i) the effect of temperature and habitat availability on both H. hippocampus and H. guttulatus behavior and (ii) the effect of temperature and an increased density of H. guttulatus (by 3×) on the activity level of congeneric species H. hippocampus. Our results showed that +3°C warming did not affect seahorse behavior in both experiments, suggesting greater behavioral tolerance to thermal variation. However, a significant reduction of the active behavior of H. hippocampus was observed when the artificial habitat was introduced in the tank, while H. guttulatus maintained its activity. Furthermore, a significant decrease of the H. hippocampus activity was observed with an increased relative dominance of H. guttulatus. Our results suggest that both increased density of H. guttulatus and habitat availability, but not ocean warming, will affect the behavior of H. hippocampus. Therefore, different interspecific behavioral strategies may occur, thus affecting the distribution of the two species among shallow habitats when they occur in sympatry.